Comparative mitogenomic analyses provide evolutionary insights into the retrolateral tibial apophysis clade (Araneae: Entelegynae) - Li, Min; Liu, Min; Hu, Shi-Yun; Luo, Fang-Zhen; Yuan, Ming-Long (Frontiers in Genetics, 2022)
The retrolateral tibial apophysis (RTA) clade is the largest spider lineage within Araneae. To better understand the diversity and evolution, we newly determined mitogenomes of ten RTA species from six families and performed a comparative mitogenomics analysis by combining them with 40 sequenced RTA mitogenomes available on GenBank. The ten mitogenomes encoded 37 typical mitochondrial genes and included a large non-coding region (putative control region). Nucleotide composition and codon usage were well conserved within the RTA clade, whereas diversity in sequence length and structural features was observed in control region. A reversal of strand asymmetry in nucleotide composition, i.e., negative AT-skews and positive GC-skews, was observed in each RTA species, likely resulting from mitochondrial gene rearrangements. All protein-coding genes were evolving under purifying selection, except for atp8 whose Ka/Ks was larger than 1, possibly due to positive selection or selection relaxation. Both mutation pressure and natural selection might contribute to codon usage bias of 13 protein-coding genes in the RTA lineage. Phylogenetic analyses based on mitogenomic data recovered a family-level phylogeny within the RTA: (((Oval calamistrum clade, Dionycha), Marronoid clade), Sparassidae). This study characterized RTA mitogenomes and provided some new insights into the phylogeny and evolution of the RTA clade.